Thermal diffusivity measurement of black and metallic graphite paint coatings - Moksin, M M; Grozescu, I V; Wahab, Z A; Yunus, W M M (IOPBristol, 1999)
The suitability of a single-access approach involving a pulsed laser technique for non-contact and non-destructive measurement of thermal diffusivity is further examined. It was used to measure the thermal diffusivity of black and metallic graphite paint coatings. The values obtained in the present work are (2.46±0.08) × 10-7 and (2.04±0.06) × 10-7 m2 s-1 for black and metallic graphite paint coatings respectively. All measurements were performed at room temperature.; The suitability of a single-access approach involving a pulsed laser technique for non-contact and non-destructive measurement of thermal diffusivity is further examined. It was used to measure the thermal diffusivity of black and metallic graphite paint coatings. The values obtained in the present work are (2.46±0.08) x 10-7 and (2.04±0.06) x 10-7 m2 s-1 for black and metallic graphite paint coatings respectively. All measurements were performed at room temperature.